O princípio do desenvolvimento sustentável nas comunidades remanescentes de quilombos - Rocha, Danilo Di Paiva Malheiros (2015)
This work aims the theme the principle of sustainable development in the quilombo´s communities. The discussion is guided by the problem of doubt whether these communities meet the sustainable development dimensions by Ignacy Sachs reputable and to what extent it would be possible. On theoretical grounds, it is outlook prepared in the international arena, through international treaties and conventions, as well as the Brazilian Federal Constitution and the orders norms. In this context, initially, are explained the historical bases of the remaining quilombo´s communities, as well as discussions on race and ethnicity, fundamental for understanding the theme. After discusses the sustainable development concept as an evolution of pure and simple development concept. Moreover, it argues that sustainable development is a legal principle, into the Brazilian Federal Constitution. Presents studies of quilombo´s communities in the Cavalcante´s city, Goiás State, the Kalunga´s Community and the Ivaporunduva´s Community, in the Eldorado´s City, São Paulo State, where the 08 sustainable development dimensions are examined: economic, ecological, social, spatial, cultural, psychological, national and international policies. It concludes that each quilombo´s community has its peculiarities and, due to the plurality from the cultural point of view, political and legal that Brazil has, are the quilombolas, through their traditional knowledge, is who will prospect the practices that lead to have sustainable development on their land because it is them who eat, live, reproduce and maintain their living cultures.